2019
DOI: 10.1101/651885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting the eQTL micro-architecture inCaenorhabditis elegans

Abstract: The study of expression quantitative trait loci (eQTL) using natural variation in inbred populations has yielded detailed information about the transcriptional regulation of complex traits. Studies on eQTL using recombinant inbred lines (RILs) led to insights on local and distant regulatory loci of transcript abundance. However, determining the underlying causal polymorphic genes or variants is difficult, but ultimately essential for the understanding of regulatory networks of complex traits. This requires ins… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…Most quantitative genetics studies in this model animal have been conducted in recombinant inbred line (RIL) panels derived from two polymorphic wild type strains, namely N2 (isolated in Bristol, UK) and CB4856 (isolated in Hawaii, USA) (1,2729). A substantial amount of phenotypic, genotypic, and high-throughput molecular data has been gathered across these recombinant inbred panels, as well as from introgression lines (30, 31) (31: PREPRINT NOT PEER REVIEWED), and many other wild isolates (3234); for a more detailed overview, see reviews (1, 35). Together, the field of quantitative genetics in C. elegans has been very productive.…”
Section: Introductionmentioning
confidence: 99%
“…Most quantitative genetics studies in this model animal have been conducted in recombinant inbred line (RIL) panels derived from two polymorphic wild type strains, namely N2 (isolated in Bristol, UK) and CB4856 (isolated in Hawaii, USA) (1,2729). A substantial amount of phenotypic, genotypic, and high-throughput molecular data has been gathered across these recombinant inbred panels, as well as from introgression lines (30, 31) (31: PREPRINT NOT PEER REVIEWED), and many other wild isolates (3234); for a more detailed overview, see reviews (1, 35). Together, the field of quantitative genetics in C. elegans has been very productive.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, comparison of eQTL profiles from multiple environments may aid our understanding of how genetic variation shapes the effects the environment has on the appearance of phenotypes [57,63,64]. In plant (Arabidopsis) and worm (Caenorhabditis elegans) model systems it has been shown that especially trans-eQTLs are dynamic and can be highly specific for a certain environment [57,[63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…Many functional polymorphisms in plants and animals, including many model species such as model nematode C. elegans, have been discovered using QTL mapping . Over the last decade molecular phenotypes such as transcript levels, protein levels and metabolites have also been used in QTL mapping [26][27][28][29][30][31][32]. Heritable variation in these molecular phenotypes often plays a role in heritable phenotypic variation [10,30,33].…”
Section: Introductionmentioning
confidence: 99%
“…Heritable variation in these molecular phenotypes often plays a role in heritable phenotypic variation [10,30,33]. Mapping expression QTLs (eQTLs) can provide insight into the transcriptional architecture of complex traits and have been conducted in model species such as Arabidopsis thaliana and C. elegans as well as several other taxa [26,[28][29][30][31][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation